Is chills an independent predictor factor for familial mediterranean fever severity score? - Bes, Cemal; Çağatay, Yonca; Ulaş, Turgay; Soy, Mehmet (BMJ Publishing Group, 2014)
[Abstract Not Available]
Keywords: Mediterranean Fever Severity; Predictor Factor; Familial